Analysis of the return in professional men's and women's padel - Escudero-Tena, A.; Ibáñez, S. J.; Vaquer Castillo, A.; Sánchez-Alcaraz, B. J.; Ramón-Llin, J.; Muñoz, D. (International Journal of Sports Science & Coaching, 2024)
The goal of this research was to analyze how situational variables such as the tactical position and the direction of the serve, the return's direction, and the score affect the vertical trajectory (VT) of the return (straight or lob) in men's and women's professional padel. For this, a sample of 2752 points (1431 men and 1321 women) corresponding to 69 matches played in the 2021 season of the World Padel Tour circuit was used. The VT of the return (straight or lob), to which player it was oriented, how important the point was attending to the score, the tactical position of the serving players, and the direction of the serve by systematic observation were recorded. The results showed that situational variables had a significant influence on the type of vertical return trajectory. Men performed a significantly higher percentage of straight returns (three out of four returns) when returning to the player at serve, or at a nonkey moment, or Australian position, or when the serve was to the body or to the side wall. In contrast, women returned a significantly higher percentage of lob returns (three out of four returns) to the server's partner, or in golden point situations, or in serves to the "T" and to the body, regardless of the tactical position at serve. The return had not been analyzed considering the score, observing changes in the golden points. These results have a great impact both on carrying out specific return training and on improving pair's anticipation to serve in different return situations.